A spectroscopic test of the rotational modulation origin of periodic Kepler photometric variability of A-type stars. Issue 2 (17th August 2020) - Sikora, J; Wade, G A; Rowe, J
ABSTRACT: High-precision space-based photometry obtained by the Kepler and TESS missions has revealed evidence of rotational modulation associated with main-sequence (MS) A- and late B-type stars. Generally, such variability in these objects is attributed to inhomogeneous surface structures (e.g. chemical spots), which are typically linked to strong magnetic fields (B100 G ) visible at the surface. It has been reported that ≈44 per cent of all A-type stars observed during the Kepler mission exhibit rotationally modulated light curves. This is surprising considering that ≲10 per cent of all MS A-type stars are known to be strongly magnetic (i.e. they are Ap/Bp stars). We present a spectroscopic monitoring survey of 44 A- and late B-type stars reported to exhibit rotational modulation in their Kepler light curves. The primary goal of this survey is to test the hypothesis that the variability is rotational modulation by comparing each star's rotational broadening ( v sin i ) with the equatorial velocities ( v eq ) inferred from the photometric periods. We searched for chemical peculiarities and binary companions in order to provide insight into the origin of the apparent rotational modulation. We find that 14 stars in our sample have v sin i > v eq and/or have low-mass companions that may contribute to or be responsible for the observed variability. Our results suggest that more than 10 per cent of all MS A- and late B-type stars may exhibit inhomogeneous surface structures; however, the incidence rate is likely ≲30 per cent.